Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1371/journal.pone.0206202
|View full text |Cite
|
Sign up to set email alerts
|

Life satisfaction favors reproduction. The universal positive effect of life satisfaction on childbearing in contemporary low fertility countries

Abstract: Do people with higher life satisfaction have more children? Having children requires considerable energy and investment on the part of parents. However, even in countries where contraceptives are easily available and widely used, where having children is optional and most of time the result of an intended action, parenthood has not gone “out of fashion”. This paper tests the hypothesis that higher life satisfaction fosters reproductive behavior. We argue that people satisfied with their overall life feel bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 42 publications
0
19
0
1
Order By: Relevance
“…Myrskylä and Margolis, 2014) may be attributable to more than the perception of an increase in happiness from the arrival of a future child -e.g. it may be the result of having a happy relationship and high life satisfaction, which are positively associated with fertility (Mencarini et al, 2018). A more in-depth exploration of personal imaginaries of parenthood, together with their relationship to childbearing desires Rytel, 2018, 2020), should be developed in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Myrskylä and Margolis, 2014) may be attributable to more than the perception of an increase in happiness from the arrival of a future child -e.g. it may be the result of having a happy relationship and high life satisfaction, which are positively associated with fertility (Mencarini et al, 2018). A more in-depth exploration of personal imaginaries of parenthood, together with their relationship to childbearing desires Rytel, 2018, 2020), should be developed in future research.…”
Section: Discussionmentioning
confidence: 99%
“…During the last decade, demo graphic research exam in ing the link between fer til ity and well-being has flourished. This lit er a ture has shown that par ent hood tends to have a pos i tive effect on sub jec tive well-being and that the quest for hap pi ness is a key deter mi nant of child bear ing in soci e ties where child bear ing is gen er ally regarded as a delib er ate choice (Balbo and Arpino 2016;Billari 2009;Margolis and Myrskylä 2015;Mencarini et al 2018). The spread and devel op ment of repro duc tive tech nology have fur ther increased indi vid u als' con trol over fer til ity deci sions by pro vid ing ADVANCE PUBLICATION infer tile cou ples with the oppor tu nity to have and raise chil dren.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of data from the British Household Panel Survey found that having children has large positive effects on life satisfaction (Angeles 2010), and that these effects become stronger as the number of children increases. Recent cross-national research has shown that high levels of life satisfaction instigate fertility, even in low-fertility countries (Mencarini et al 2018), although this relationship can vary depending on individual factors and across institutional contexts. Based on data from a large number of OECD countries, Glass and others (2016) found large variations in the happiness of parents, depending on the generosity of family policies.…”
Section: Individual Socio-economic Demographic and Behavioural Differences In Swb Levels And Time Variationsmentioning
confidence: 99%